Comparison of the short-term outcomes between Y-incision aortic annular enlargement and traditional aortic annular enlargement techniques - Makkinejad, Alexander; Hua, Joanna; Hassler, Kenneth R.; Monaghan, Katelyn; Kim, Karen; Fukuhara, Shinichi; Patel, Himanshu J.; Yang, Bo (Annals of Cardiothoracic Surgery; Vol 13, No 3 (May 31, 2024): Aortic Annular Enlargement, 2024)
Background: The short-term efficacy and safety of the Y-incision technique of aortic annular enlargement (AAE) has been established. We aimed to determine how the short-term outcomes of the Y-incision technique compared to traditional AAE techniques. Methods: From February 2011 to June 2022, 380 patients at the University of Michigan Hospital underwent aortic valve replacement (AVR) with AAE using either traditional annular enlargement techniques (Traditional group, n=270), including Nicks [63% (171/270)], Manouguian [34% (91/270)], and others [3% (8/270)], or the Y-incision technique (Y-incision group, n=110). Propensity score matching was performed by controlling for age, sex, body surface area (BSA), hypertension, diabetes, dialysis, chronic lung disease, stroke, prior cardiac surgery, primary indication, operative status, concomitant procedures, and prosthesis type, to generate a balanced cohort of 103 pairs. Results: There were no differences in demographics, comorbidities, primary indications of the operations, or concomitant procedures between the matched groups. The median native aortic annulus diameter, measured in the operating room, was 21 mm for both groups. Median prosthesis size was 23 in the Traditional group, and 27 in the Y-incision group (P